TRANSFORMATION OF IJARAH CONTRACT: The Review of The Concept and Its Implementation in Islamic Banking - Ade Nur Rohim; Atang Abdul Hakim (IAIN Ponorogo, 2023)
Innovations in sharia banking products and services in Indonesia continue to experience significant developments. This is important to do to answer the needs of recent financial transactions. Various financing products with various contracts have been applied by Islamic financial institutions. One of the products developed is ijarah-based financing. However, different viewpoints regarding the legal validity of ijarah with its various types are still being discussed among academics and practitioners. The concept of ijarah itself was practiced in early Islamic era and continues to be practiced today in various contemporary financial transactions. This study aims to review the process of transforming ijarah principles to the development of their varieties, as well as related legal and regulatory provisions as a basis for implementation in the development of financing products in Islamic banking and finance. This research was a qualitative research using a literature study approach with descriptive analysis. This study concludes that several texts from the al-Qur'an and Sunnah explain the concept of ijarah and its permissibility according to sharia. Nash explains at least two types of ijarah, namely ijarah in service and asset leases. Both were revealed in the provisions contained in the KHES, PBI, as well as several DSN MUI fatwas. These regulations form the basis for implementing ijarah, IMBT, and IMFD in various sharia banking products and services.